The economies of the Soviet bloc : a study of decision making and resource allocation - Wellisz, Stanislaw (New York : McGraw-Hill, 1964)
The study is a primer of soviet-type economics for the Western reader. It is designated for those who do not wish to acquire specialized knowledge, yet who would like to know about the role of consumers and workers, about the role of the Communist Party leadership and planners, and about planning objectives and methods behind the Iron Curtain.
Includes bibliographical footnotes and index.
rpm 31/10/2017
Loans
Keywords: Economic policy; Europe, Eastern